Assignment box alert for student (ABA) - Azizul, Aziz (2011)
Client-server is a network model for computer networking that utilizes client and server devices each designed for specific purpose.The client-server model can be used on the internet as well as local area network (LAN). Client-server networking grew in popularity many years ago as personal computers (PC) became alternative to older mainframe computers.The client-server model distinguishes between applications as well as devices. Network client make requests to a server by sending messages,and servers responds to their clients by acting on each request and returning results.Before this,the submission assignments from the students were manually submitted using the hardcopy (printing material) or by softcopy (Compact Disc (CD)),which is taking time and very easily being damaged or misplace.In this project,this client-server application will help the student in their assignment submission.It also will make the submission faster than ever.Therefore,it will make the data of the participant can be view more systematically by the lecturer. Besides that,with the notification system,the student can alert the uploaded assignment by their lecturer.